Challenges Associated with Negative Pressure Pulmonary Oedema: A Case Report and Review - Wing Hoh Loo; Kay Mint Goh (The Journal of Medicine, Law & Public Health)
Negative pressure pulmonary oedema (NPPO) is a rare but serious complication for patients undergoing general anaesthesia. It often presents a diagnostic dilemma, thus posing significant management challenges. Despite the complexity of diagnosis, the pathophysiology and management of NPPO have been extensively studied. We present a case of NPPO in a middle-aged obese patient with high perioperative cardiac risk who underwent an emergency open appendicectomy. This case report details the anaesthetic approach to managing the patient’s complex comor-bidities, the series of events leading to the diagnosis, and subsequently the management of NPPO. We dis-cuss the challenges encountered in diagnosing and managing NPPO, and review potential preventive measures. Our conclusion underscores that diagnosis of NPPO remains challenging, and early identification of patients at risk with vigilant monitoring is crucial for timely diagnosis and effective management.